Unravelling a trichloroacetic acid-catalyzed cascade access to benzo[f]chromeno[2,3-h]quinoxalinoporphyrins - Tekuri, Chandra Sekhar; Singh, Pargat; Nath, Mahendra (Beilstein Journal of Organic Chemistry, 2023)
A facile one-pot four-component synthetic methodology is evolved to construct novel copper(II) benzo[f]chromeno[2,3-h]quinoxalinoporphyrins in good yields via a sequential reaction of copper(II) 2,3-diamino-5,10,15,20-tetraarylporphyrins, 2-hydroxynaphthalene-1,4-dione, aromatic aldehydes, and dimedone in the presence of a catalytic amount of trichloroacetic acid in chloroform at 65 °C. Further, the newly prepared copper(II) porphyrins were transformed to the corresponding free base and zinc(II) benzo[f]chromeno[2,3-h]quinoxalinoporphyrins under standard demetallation and zinc insertion conditions. The absorption and emission properties of the obtained porphyrins were investigated by using UV–visible and fluorescence spectroscopy. The preliminary photophysical results revealed a significant red-shift in their absorption and emission spectra as compared to the meso-tetrakis(4-methylphenyl)porphyrins due to the extended π-conjugation.
Keywords: bathochromic shift; benzo[f]chromeno[2,3-h]quinoxalinoporphyrins; catalysis; multicomponent synthesis; one-pot reaction; trichloroacetic acid